(untitled) (Journal of Bio-Science, 2026)
The phenylalanine ammonia-lyase (PAL) gene family plays a pivotal role in plant secondary metabolism, particularly within the phenylpropanoid pathway that produces essential metabolites contributing to plant growth, defense, and fruit quality. This study presents a comprehensive genome-wide analysis of the PAL gene family in Fragaria × ananassa Duch. (Strawberry) to elucidate their evolutionary relationships, chromosomal distribution, regulatory mechanisms, and potential involvement in abiotic and biotic stress responses. Eight PAL genes (designated FaPAL1–FaPAL8) were identified and systematically characterized. Gene duplication analysis revealed evolutionary relationships among FaPAL members and suggested possible functional redundancy. Phylogenetic analysis of FaPAL proteins with those from five other plant species clustered the genes into distinct clades, indicating both functional diversification and evolutionary conservation. Conserved motif analysis confirmed the presence of key domains required for PAL enzymatic activity, while promoter analysis uncovered numerous cis-regulatory elements associated with light responsiveness, hormonal regulation, and abiotic stress tolerance (including drought and temperature stress). Furthermore, microRNA (miRNA) interaction analysis indicated that FaPAL3 and FaPAL5 exhibited the highest miRNA targeting frequency (38.9%; score 7), highlighting their potential regulatory significance under stress conditions. Overall, this study provides valuable insights into the structural, evolutionary, and functional dynamics of the PAL gene family in strawberry. The findings lay a foundation for future genetic and biotechnological interventions aimed at enhancing fruit quality, disease resistance, and stress resilience for sustainable strawberry cultivation. J. Bio-Sci. 34(1): 01-11, 2026